2014
DOI: 10.4028/www.scientific.net/msf.787.387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pure Dicalcium Silicate Powder by the Pechini Method and Characterization of Hydrated Cement

Abstract: Calcium silicate (CS) is a main component of Portland cement and is responsible for the strength development. Recent research has shown that dicalcium silicate cement (CSC) is bioactive and is a potential candidate for bone replacement. Traditionally, dicalcium silicate powder is synthesized by a solid state reaction or a sol-gel method. The solid-state reaction, however, usually needs a higher temperature and a longer calcination time. Furthermore, the dicalcium silicate powder made by the sol-gel method is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It indicates that the MC3T3 cells spread and proliferate better on 7S3A than on 3S7A, which can be attributed to the more content of Si in 7S3A. Previous studies 12,28 have reported that Si can be released from CSC prepared using pure β-Ca 2 SiO 4 . Figure 7 shows the silicon release results of 3S7A and 7S3A cement.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…It indicates that the MC3T3 cells spread and proliferate better on 7S3A than on 3S7A, which can be attributed to the more content of Si in 7S3A. Previous studies 12,28 have reported that Si can be released from CSC prepared using pure β-Ca 2 SiO 4 . Figure 7 shows the silicon release results of 3S7A and 7S3A cement.…”
Section: Resultsmentioning
confidence: 83%
“…The concentrations of the released silicon were calculated by using the same calibration curve that was reported in our previous work. 12…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literatures revealed that larnite was prepared by sol‐gel method, [17] solid state route, [18] Pechini method [19] at higher temperatures. Previous findings divulged that sol‐gel combustion method assisted in synthesizing pure larnite at 900 °C using citric acid as fuel [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The calcium content in the larnite was found to be twice as compared to wollastonite which could induce faster apatite deposition better than wollastonite when exposed to the physiological environment. [15,17] Recent literatures revealed that larnite was prepared by solgel method, [17] solid state route, [18] Pechini method [19] at higher temperatures. Previous findings divulged that sol-gel combustion method assisted in synthesizing pure larnite at 900 °C using citric acid as fuel.…”
Section: Introductionmentioning
confidence: 99%